Afrofuturism. - Bennett, Michael (Computer (00189162), 2016)
Science fiction prototyping is strengthened by the diverse voices that inform the process. One science fiction genre exploring fascinating, engaging, and often challenging visions of tomorrow is Afrofuturism.